Habilidades de lectoescritura a través de estrategias lúdicas como función mediadora en estudiantes de tercer año de educación general básica en la escuela de educación básica Luis Aurelio González” de la ciudad de Guaranda, provincia Bolívar durante los meses octubre 2023-febrero 2024 - Punina Toalombo, Vanessa Marisol (2024)
In this final research report, conducted at the "Luis Aurelio González" Educational Unit in the Guaranda canton, Bolívar province, during the period from September to February 2024, the aim is to address difficulties in literacy through the implementation of playful strategies as a mediating function in third-year Basic Education students. The main objective is to assess the effectiveness of these strategies in improving learning in this specific aspect. Preliminary results indicate that the application of playful strategies can have a positive impact on the development of literacy skills in students. This study is framed within a pedagogical approach aimed at promoting active participation and interest of students in the learning process. It is expected that the findings of this research will significantly contribute to the improvement of educational practices in the area of literacy, promoting more inclusive and effective learning for all students